A Systematic Review on Environmental Factors associated with Autism Spectrum Disorder in Bangladesh - Khan, Md Shahid; Tareq, Shafi Mohammad; Kabir, Mohammad Alamgir (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Exposure to different environmental factors appears to be widespread, detrimental to human brain development and a potential risk factor for autism spectrum disorder (ASD). We conducted a systematic review on the relationship between environmental factors and ASD in Bangladesh. Methods: This paper reviews the evidence on modifiable environmental factors that have been associated, in some studies, with ASD, including socio-demographic and physical environmental factors exposures during prenatal and postnatal periods. Besides, this review is restricted to human studies with at least 50 cases of ASD, having a valid comparison group, conducted within the past two decades. Moreover, literatures searched using three electronic databases (PubMed, Google Scholar, and Biomed Central) from August 2020 to January 2021, based on the PRISMA guidelines. Literatures screened by two distinguished reviewers (Khan MS; Tareq SM), and resolved differences by consensus and further discussion with third reviewer based on requirements. Then selected the eligible 21 studies based on inclusion criteria’s. Two of the reviewers independently screened articles, extracted data for descriptive information and assessed risk of bias by using the Newcastle-Ottawa scale (NOS). Results: There is no article found with poor quality in NOS. The overall quality of the studies is high. There are strong association between ASD risk and some factors such as advanced maternal age, lead exposure during pregnancy and early childhood, blood Arsenic level of ASD children. Though few factors are related to increased risk of ASD; so far, no specific environmental factor has been found associated with increased risk of ASD with large power of study. Conclusion: There is appears to be a lack of such type of study in developing countries like Bangladesh. Therefore, nationwide widespread research needed to address the modifiable environmental risk factors for ASD. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 237-248